THE RELIGIOUS HARMONY OF BANDA'S CAKALELE CULTURE: A TOUCH OF ASIAN, MIDDLE EASTERN, AND EUROPEAN ACCULTURATION (Journal of Namibian Studies : History Politics Culture, 2023)
Cultural acculturation allows interaction and exchange between different cultural groups. Mixing Asian, Middle Eastern, and European cultures has also resulted in the acculturation of a "new culture" known as Banda Culture. One is Cakalele Banda, which appears to have a multi-ethnic flavor; Asia, Arabia, and Europe are intertwined in one series of rituals. Banda Cakalele has its uniqueness among other types of Maluku Cakalele. Starting from the clothes, the formation of dancers, and the movements show a specific orientation regarding spiritual values, social, and coastal environment. This research uses qualitative historical and phenomenological analysis. The analysis results include acculturation in traditional dress, movements, and dances, musical instruments, context and meaning, and aspects of the noble values of Banda customs. This research provides a deeper understanding of the origins, development, and cultural interactions in Cakalele Banda. It helps to understand the performance's historical, religious, and cultural context. It also reveals the relationships and cultural influences between Cakalele Banda and Asian, Middle Eastern, and European cultures.